Use of the system „Pyramid-V" for the decision of tasks of prognostication of Ukraine gas industry development - Leshchenko I.Ch.; Spitkovskyi A.I. (General Energy Institute of the National Academy of Sciences of Ukraine, 2010)
On the modern stage a Ukraine economy power sector is under the action of such processes, as globalization, fuel and energy resources markets liberalization, negative influence on an environment strengthening and increasing inflexibilities of ecological limitations and requirements. In these terms the computer-based system „Pyramid-V" is created in Institute of General Energy of National Academy of Sciences of Ukraine for determination organizational, economic and technical measures priority of steady development providing both domestic fuel and energy complex on the whole and his separate industries, in particular gas industry.Subsystem „Matrix" is one constituents of „Pyramid-V". It allows decide the linear programming with boole variables tasks with the use of linear programming resources kit GLPK. The gas industry development prognostication belongs to this class of linear programming tasks. The renewed model of gas-supplying system development prognostication which takes into account the market economy features and requirement of negative influence on an environment minimization is realized in „Matrix".Using the developed programmatic facilities the natural gas transporting and beginning/selection costs for the concrete terms of every Ukrainian main gas pipelines compressor department were expected. The prognosis of Ukrainian gas-transport system's objects reconstruction is formed.